Relationship between endothelial dysfunction and cardiovascular risk factors and the extent and severity of coronary artery disease - Hilal Kurtoğlu Gümüşel; Alp Burak Çatakoğlu; Özlem Yıldırımtürk; Selen Yurdakul; Funda Helvacıoğlu; Murat Ziyrek; Ruken Hanavdeloğulları; Vedat Aytekin; Saide Aytekin (KARE Publishing, 2014)
Objective: Endothelial dysfunction (ED) is associated with coronary artery disease (CAD) and cardiovascular risk factors. The relationship between cardiovascular risk factors, ED and the presence, extent and severity of CAD, was evaluated in patients with and without angiographically defined CAD in our study. Method: Eighty patients with CAD and 20 subjects with normal coronary arteries were included. Endothelial function was evaluated by endothelium-dependent flow-mediated dilatation (FMD) and nitroglycerine mediated dilatation (NMD) measurements, using brachial artery Doppler ultrasonography (USG). Cardiovascular risk factors were identified. The extent and severity of CAD was determined via vessel and modified Gensini scores. Results: FMD% and NMD% were significantly decreased in the CAD(+) group compared with the CAD(-) group (p=0.0001). In the CAD(+) group, the cut-off values of FMD% and NMD% in distinguishing between single-vessel and multi-vessel diseases were 8.5% (sensitivity: 95%, specificity: 62%) and 13.6% (sensitivity: 91%, specificity: 62%), respectively. Additionally, modified Gensini score was significantly correlated with both FMD and NMD (r=-0.825, r=-0.778, respectively, p=0.0001) in the CAD(+) group. Conclusion: Endothelial dysfunction was more prevalent in the CAD(+) group and degree of ED correlated well with the extent and severity of CAD.